(untitled) - Bilgen Sağ; F. Işıl Bilican (Psikiyatride Güncel Yaklaşımlar, 2020)
This study investigated whether resilience mediated the relationship between cognitive factors (maladaptive schemas and positive perception) and psychological symptoms (depressive symptoms and wellbeing). Two hundred thirty one young adult participants were administered the Young Schema Scale, Positive Perception Scale, Resilience Scale for Adults, Beck Depression Scale, and Warwick and Edinburg Mental Wellbeing Scale. The participants’ ages ranged from 18 to 30. The Disconnection/Rejection and Impaired Autonomy/Performance schema domains predicted depressive symptoms. The Disconnection/ Rejection, Impaired Autonomy/Performance, Other-Directedness and Overvigilance/Inhibition schema domains predicted wellbeing. Psychological resilience fully mediated the relationship between Overvigilance/Inhibition schema domain and depressive symptoms, and partially mediated the relationship between the Impaired Autonomy/Performance schema domain and depressive symptoms. Psychological resilience fully mediated the relationship between the Disconnection/Rejection, Impaired Autonomy/Performance schema domains, and well-being. High levels of positive perception enhanced psychological resilience and wellbeing, and reduced depressive symptoms. When individuals were psychologically resilient, they did not feel depressed even if they demonstrated an Overvigilance and Inhibition Schema. Individuals sustained well-being when they were resilient, even if they scored high on the Disconnection/Rejection and Impaired Autonomy/Performance schema domains. The findings indicated that psychological resilience could protect individuals from feelings of depression only in the presence of certain maladaptive schemas.